Evolution of plant virus movement proteins from the 30K superfamily and of their homologs integrated in plant genomes - Mushegian, Arcady R.; Elena, Santiago F. (Virology (New York, N.Y.), 2015)
Homologs of Tobacco mosaic virus 30K cell-to-cell movement protein are encoded by diverse plant viruses. Mechanisms of action and evolutionary origins of these proteins remain obscure. We expand the picture of conservation and evolution of the 30K proteins, producing sequence alignment of the 30K superfamily with the broadest phylogenetic coverage thus far and illuminating structural features of the core all-beta fold of these proteins. Integrated copies of pararetrovirus 30K movement genes are prevalent in euphyllophytes, with at least one copy intact in nearly every examined species, and mRNAs detected for most of them. Sequence analysis suggests repeated integrations, pseudogenizations, and positive selection in those provirus genes. An unannotated 30K-superfamily gene in Arabidopsis thaliana genome is likely expressed as a fusion with the At1g37113 transcript. This molecular background of endopararetrovirus gene products in plants may change our view of virus infection and pathogenesis, and perhaps of cellular homeostasis in the hosts. •Sequence region shared by plant virus “30K” movement proteins has an all-beta fold.•Most euphyllophyte genomes contain integrated copies of pararetroviruses.•These integrated virus genomes often include intact movement protein genes.•Molecular evidence suggests that these “30K” genes may be selected for function.